Development and study of technological visual programming of logic control problems - Furman, Ilya; Allashev, Alexander; Piskarev, Aleksey; Bovchaliuk, Stanislav (Eastern-European Journal of Enterprise Technologies, 2017)
The approach to logic control programming using a technological language was described. It is based on the use of a tabular cyclogram directly as a programming language. It was shown that using a cyclogram, it is possible to describe the complete algorithm of logic control of industrial equipment, and with its use to generate automatically a program code in standard languages of programming of industrial controllers. This approach will make it possible to involve engineers-technologists, who are the most competent experts in the field of automated process, in the process of developing and debugging of control programs. The benefits of technological visual programming in comparison with the conventional approach to control programming were described. The requirements for the necessary structure of a specialized programming environment with the use of a tabular language of technological cyclograms were stated. During experiments in the developed environment, the authors described in the cyclogram language the algorithm of controlling a portal industrial robot, by which a specialized translator automatically generated the complete program code in the language of IEC 61131-3 standard for PLC microprocessor. In addition, within the proposed approach, the authors described the possibility to generate automatically a complete description of a logical controlling automatic machine of increased reliability in HDL-language using the same cyclogram and the template. Technological visual programming makes it possible to involve engineers-technologists directly in the process of control programming, which decreases labor consumption of developing control systems and enhances the quality of a program code. The technological cyclogram itself can be widely used by various specialists at the stages of launch-adjusting operations, maintenance and modernization of control systems, and as technical documentation during the operational phase